2014
DOI: 10.1262/jrd.2014-066
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among antral follicular echotexture, apoptosis and expression of key steroidogenic enzymes in sheep

Abstract: Nineteen cycling ewes underwent transrectal ultrasonography of ovaries followed by ovariectomies during the growth phase of the first follicular wave of the interovulatory interval or the proestrus/estrus phase of the cycle. Quantitative ultrasonographic characteristics of the antrum and follicular wall in a total of forty-three ovine antral follicles were examined for correlations with the protein expression of three steroidogenic enzymes (cytochrome P450 17α-hydroxylase, CYP17; cytochrome P450 aromatase, CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…All these changes in pulmonary histophysiology may be associated with the gradual decrease in NPV values that was observed between 120 and 24 h before whelping in the present study; the terminal stages of growth and secretory activity of connective tissue ducts appear to be inversely related to pixel intensity of the tissue (Giffin et al, 2009(Giffin et al, , 2014. Similarly, an increase in NPVs just prior to parturition may be associated with the saccular phase of foetal lung development (Lourenço and Machado, 2013), reflecting the biochemical and functional adaptations that occur during lung maturation (Benson et al, 1983;Nicholas et al, 1986;Adler et al, 1990), specifically, the reduction in total protein content (Ahmadi et al, 2013) and augmentation of enzymatic activity (VanDuzer et al, 2014). Results of the present study, however, are inconsistent with those reported by Banzato et al (2017), where there was an abrupt increase in pulmonary echogenicity during the canalicular phase and a plateau during the saccular phase of foetal lung development in various large dog breeds.…”
Section: Discussionsupporting
confidence: 51%
“…All these changes in pulmonary histophysiology may be associated with the gradual decrease in NPV values that was observed between 120 and 24 h before whelping in the present study; the terminal stages of growth and secretory activity of connective tissue ducts appear to be inversely related to pixel intensity of the tissue (Giffin et al, 2009(Giffin et al, , 2014. Similarly, an increase in NPVs just prior to parturition may be associated with the saccular phase of foetal lung development (Lourenço and Machado, 2013), reflecting the biochemical and functional adaptations that occur during lung maturation (Benson et al, 1983;Nicholas et al, 1986;Adler et al, 1990), specifically, the reduction in total protein content (Ahmadi et al, 2013) and augmentation of enzymatic activity (VanDuzer et al, 2014). Results of the present study, however, are inconsistent with those reported by Banzato et al (2017), where there was an abrupt increase in pulmonary echogenicity during the canalicular phase and a plateau during the saccular phase of foetal lung development in various large dog breeds.…”
Section: Discussionsupporting
confidence: 51%
“…In the search for alternative, non-invasive methods of embryo assessment, our study employed the phototexture analysis of ovine embryos. The term phototexture refers to the visual quality of the surface of an object, revealed through variances in contrast and tone (Vanduzer et al, 2014). In the past, phototexture could only be examined visually, but presently pixel intensity and uniformity of digital images can be assessed using computerized image analysis.…”
Section: Introductionmentioning
confidence: 99%